Pendampingan Pemahaman Fintech pada UMKM Makanan di Kabupaten Banyumas - Triani Arofah; Wita Ramadhanti; Oman Rusmana (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2026)
This study describes a mentoring process aimed at building fintech understanding among food micro, small, and medium enterprise (MSME) owners in Banyumas Regency who are registered GrabFood partners but lack merchant-side understanding of OVO payment processing and QRIS verification. Using a descriptive qualitative case study approach, the research team acted as consumers ordering through the GrabFood Self-Pickup feature, paying via OVO, and directly observing how MSME owners handled, verified, and responded to digital payment transactions before and after guided mentoring. This study also incorporates survey data from 34 MSME respondents to characterize the broader profile of fintech understanding among food MSMEs in the region. Findings show that most owners initially adopted a passive